Microscopic and molecular detection of Cytauxzoon spp. in cats in Mosul city, Iraq - Sura S. Aghwan; Enas S. Hussein; Salam A Esmaeel (Iraqi Journal of Veterinary Sciences)
The study aims to diagnose Cytauxzoon spp. in affected stray cats in Mosul. To achieve this goal, microscopic and conventional polymerase chain reaction technology was used, and the genetic analysis of Cytauxzoon spp. was verified. Blood samples were collected from 50 stray cats in various city areas. The infection rate of Cytauxzoon spp. among cats in Mosul city was 76% (38/50). Using single sequence analysis, a single Cytauxzoon felis sequence was discovered in Nineveh Governorate for the first time. One of these sequences was submitted to GenBank with the entry number LC775709.1. The results indicate that some of the tested samples contain DNA from the Cytauxzoon genus, based on the presence of bands at the expected 1600 bp size. The local genome sequence of Cytauxzoon felis Sesa LC775709.1 is highly similar to sequences found in geographically diverse regions such as Switzerland, Italy, France, and the USA. According to the study, the infection rate of cats with Cytauxzoon spp parasites in Mosulwas significant, reaching 76%. The results of genetic sequencing were presented for the first time. One novel isolate was discovered: the Cytauxzoon felis Sesa gene LC775709.1 for 18S rRNA. The phylogenetic tree was constructed, and it was discovered that the local sequence LC775709.1 is very closely related genetically to the sequences from Europe and the USA while showing some genetic differences with the sequences from Brazil and South Africa.